Unternehmensrestrukturierung im Umbruch?!: europäische und internationale Herausforderungen - Ebke, Werner F.; Seagon, Christopher; Blatz, Michael (Deutsches, europäisches und vergleichendes Wirtschaftsrecht, 2017)
The publication assembles speeches that were given at the 10th Heidelberg Symposium on Corporate Restructuring in March 2017. The contributions deal, amongst others, with various aspects of the recent European Commission’s Proposal for a directive on preventive restructuring frameworks, possible effects of the Brexit on English schemes of arrangement that have been used in the past by several German companies, questions of the restructuring of banks and the role of the German Bundesbank in the international financial crisis. The increasing European and international challenges for the professional education in the field of corporate restructuring form an additional subject of the symposium. An extensive summary of the presentations, discussions and conclusions complete the volume.With contributions by:Manfred Balz, Christoph Bentele, Patricia Godfrey, Peter Hommelhoff, Stephan Madaus, Florian T. Millner, Myriam Roth, Robert Scheel, Christopher Seagon und Carl-Ludwig Thiele.
Gesehen am 06.12.2017
Vorträge anlässlich des zehnten Heidelberger Symposiums zur Unternehmensrestrukturierung ... am 23. März 2017 in der Neuen Aula der Universität Heidelberg
Keywords: Konferenzschrift -- 23.03.2017 -- Heidelberg; Aufsatzsammlung; Restrukturierung; Organisation; Unternehmen; Deutschland; Europäische Union